Computer-Aided Wire Design using Sheet Metal Feature for Dentistry Applications - Hamid, R.A.; Ito, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This study approximates a dentistry wire bending operation by means of sheet metal feature. In reality, the sequence of bending operation depends on the target shape and determined manually by the dental technician. Sometimes, the technician needs to perform multiple bends at several bend points to fit the patient’s tooth morphology. These cumbersome procedures could be improved if the use of computer-aided design (CAD) and computer-aided manufacturing (CAM) is applied in this field, with the aid of a proper process planning in between. In order to do so, the wire design has to be established and subsequently utilized for the bending code (B-code) generation. Therefore, the recent study describes the bending operation for a selected dentistry wire, in relation to the bending points and bending parameters. Then, a 3D comparison between a digitized polygonal model and the sheet metal model was executed in Geomagic to inspect the deviation. The color-mapping result showed a clear divergence between the test model and the reference model as a result of design complexity. The limitation of this outcome could be further improved by designing the wire as detailed as possible towards the scanned teeth.